Ectopic Thymus: An Unusual Case of Subglottic Mass. (December 2019) - Paraboschi, Irene; Fati, Federica; Rizzo, Francesca; Sacco, Oliviero; Stagnaro, Nicola; Mattioli, Girolamo; Simonini, Alessandro; Mazzei, Oscar; Torre, Michele
Objectives: The aim of our study is to report a case of a child with subglottic thymus that was suspected during diagnostic work-up for severe airway obstruction, excised surgically and confirmed with final histopathological examination. Moreover, we performed a narrative literature review to outline clinical and diagnostic features of this rare condition and to report suggestions for the management of subglottic masses. Methods: We report the case of a 7-month-old boy who was admitted to our Pediatric Airway Team Unit due to a history of worsening biphasic stridor and recurrent episodes of upper airway obstruction. The successful diagnostic work-up and a narrative literature of analogous cases of subglottic thymus were reported. Results: Ectopic thymus is a very rare condition in which thymic tissue is found outside the normal pathway of its embryonic migration. It usually presents as a cystic or, more rarely, solid mass, showing an indolent course toward spontaneous involution. In some cases, however, it becomes symptomatic exerting compression on surrounding vital structures. Due to its rarity, the initial diagnosis is normally mistaken with inflammatory diseases or malignancies and the definitive diagnosis is only achieved after histological examination of the excised specimen. To our knowledge, only four other cases of subglottic ectopic thymic tissue have been reported in the English literature so far and the diagnosis has never been suspected preoperatively. Conclusion: It is mandatory to consider ectopic thymic tissue in the differential diagnosis in children presenting with airways obstruction in order to prevent unnecessary, extensive, and exploratory surgery.